Electrochemical Investigation of Interfacial Properties of Ti3C2Tx MXene Modified by Aryldiazonium Betaine Derivatives - Lorencova, Lenka; Gajdosova, Veronika; Hroncekova, Stefania; Bertok, Tomas; Jerigova, Monika; Velic, Dusan; Sobolciak, Patrik; Krupa, Igor; Kasak, Peter; Tkac, Jan (Frontiers in Chemistry, 2020)
For efficient and effective utilization of MXene such as biosensing or advanced applications interfacial modification of MXene needs to be considered. To this end, we describe modification of Ti3C2Tx MXene by aryldiazonium-based grafting with derivatives bearing a sulfo- (SB) or carboxy-(CB) betaine pendant moiety. Since MXene contains free electrons, betaine derivatives could be grafted to MXene spontaneously. Kinetics of spontaneous grafting of SB and CB towards MXene was electrochemically examined in two different ways and such experiments confirmed much quicker spontaneous SB grafting compared to spontaneous CB grafting. Moreover, a wide range of electrochemical methods investigating non-Faradaic and Faradaic redox behaviour also in presence of two redox probes together with contact angle measurements and secondary ion mass spectrometry (SIMS) confirmed substantial differences in formation and interfacial presentation of betaine layers, when spontaneously grafted on MXene. Besides spontaneous grafting of CB and SB towards MXene, also electrochemical grafting by a redox trigger was performed. Results suggest that electrochemical grafting provides denser layer of SB and CB on the MXene interface compared to spontaneous grafting of SB and CB. Moreover, electrochemically grafted SB layer offers much lower interfacial resistance and electrochemically active surface area compared to electrochemically grafted CB layer. Thus, by adjusting SB/CB ratio in the solution during electrochemical grafting it is possible to effectively tune redox behaviour of MXene modified interface. Finally, electrochemically grafted CB and SB layer on MXene were evaluated against non-specific protein binding and compared to anti-fouling behaviour of unmodified MXene interface.